Quality of Life of Melasma Patients in Pakistan - Rahman, Atiya; Basit, Anam; Mohsin, Sadia; Ahmed, Najia; Tahir, Moizza; Ishfaq, Asim (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the quality of life in Pakistani melasma patients. Study Design: Cross-sectional study. Place and Duration of Study: Department of Dermatology, Combined Military Hospital Lahore, from Oct 2020 to May 2021. Methodology: The study was conducted on 126 adult patients of both genders by non-probability, consecutive sampling technique. Melasma severity was assessed by ’melasma area severity index (MASI) and quality of life impairment by ’dermatology life quality index (DLQI). Results: A total of 126 patients participated in the study, out of which 85.7% were females, and 14.3% were males. Mean MASI score was 12.21 ± 6.87, and mean DLQI score was 8.22 ± 7.46. Male patients had higher MASI scores and statistically signifycant DLQI than female patients (p=0.016). Employed people and those from the higher socio-economic group showed a more significant impairment of their quality of life. Conclusion: There was moderate impairment of quality of life in melasma patients. Healthcare givers need to recognize the effect of melasma on mental health while counselling patients and devising management strategies.